Correlation Of Psychosomatic Factors And Personality Traits With The Severity Of Hidradenitis Suppurativa - Kontoangelos, Konstantinos; Foulou, Foteini Dionysia; Tsiori, Sofia; Papageorgiou, Charalabos; Stratigos, Alexander; Liakou, Aikaterini I (Dermatology Practical & Conceptual, 2025)
Introduction: Hidradenitis suppurativa is a disease with a decisive burden on sufferers, both physical and psychological. It was expected that the more intense the severity of symptoms the patients experienced, the greater the correlation with the psychosomatic manifestations would be. Objectives: The present study aimed to explore the correlation between hidradenitis suppurativa and the psychosomatic burden, the personality, and the demographic characteristics of the participants. Methods: The participants were 90 outpatients of the hospital, aged 18 to 65, who had been diagnosed with hidradenitis and were sufficiently proficient in Greek. The psychometric instruments administered were the Symptom Checklist-90 (SCL90), the Beck Depression Inventory (BDI), the Eysenck Personality Questionnaire (EPQ), the short-form McGill Pain Questionnaire (SF-MPQ), the Hurley and refined Hurley classifications, the International Hidradenitis Suppurativa Severity Scoring System (IHS4), and a short demographic questionnaire. All statistical analyses were performed using the SPSS-28 statistical package. Results: According to statistical analyses, there was no statistically significant relationship between disease severity, psychosomatic burden, and personality. However, there were statistically significant associations with demographic factors, such as being female or not being in a relationship, the patient’s body mass index, the locus of the skin lesion, a history of hospitalization, comorbidities, psychiatric history, and pain with psychopathological manifestations and personality. Conclusions: It is important that further research be conducted that will include more mental disorders besides anxiety and depression while at the same time excluding confounding factors for safer interpretation of the results.